2016
DOI: 10.1007/s13760-016-0732-0
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of the ketogenic diet in infants and young children with refractory epilepsies using a formula-based powder

Abstract: To evaluate the efficacy, safety, and tolerability of a classic 4:1 ketogenic diet using a formula-based powder in infants and children with refractory seizures who are reluctant to eat homemade foods. We conducted an open label trial and administered a ketogenic diet using formula-based power (Ketocal). Twenty-seven infants and children aged between 12 months and 5 years were enrolled who had refractory seizures and were reluctant to eat homemade foods. Of 27 children, 5 were lost to follow-up and 22 were rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…In our study, 83.70% patients followed a 2:1 KD ratio, and 78.26% responded to the KD by the rst month of treatment. Our ndings are consistent with those of some previous studies [10][11][12][13] but different from others [14,15] . Our study included a greater number of children who exhibited improvement and whose seizures were managed while following the 2:1 KD ratio.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, 83.70% patients followed a 2:1 KD ratio, and 78.26% responded to the KD by the rst month of treatment. Our ndings are consistent with those of some previous studies [10][11][12][13] but different from others [14,15] . Our study included a greater number of children who exhibited improvement and whose seizures were managed while following the 2:1 KD ratio.…”
Section: Discussionsupporting
confidence: 84%
“…In this sense, prolonged seizures or status epilepticus in epilepsy patients can become a serious problem due to their consequences on the quality life from this population [50]. Seizures can have devastating consequences and, as result, suffer bodily injury requiring hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…Seizures can have devastating consequences and, as result, suffer bodily injury requiring hospitalization. Others have shortened life span due to the increased risk of unexpected sudden death that is associated with uncontrolled seizures [50][51][52]. Studies have shown that patients with epilepsy can be significant neuropsychological, psychiatric, and social impairments that limit employment, reduce marriage rates, and decrease quality of life [51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…For older children and adults, it can be used as a meal substitute and in combination with solid foods, to increase the KR of a meal or to supplement it with vitamins and minerals. Several studies have shown that the use of powder ketogenic formula in KDs is effective, safe, and tolerable for infants and children suffering refractory seizures [119,120]. In a recent study, 27 infants and children with drug-refractory epilepsy, aged between 12 months and five years, were treated with a powder ketogenic formula for four months.…”
Section: Food Products For the Ketogenic Dietmentioning
confidence: 99%